The use of Melody and Harmony Elements as Techniques in 20th Century Music (Raparin Journal of Humanities (RJH), 2024)
This publication is a descriptive-analytical study, Depends on qualitative method. Describes a specific phenomenon or event or thing, depending on the books and sources include examples, and analysis of those examples that are related to the innovations that occurred in the common materials (melody-harmony) used in the twentieth century, and how it was used as a new technique in music.The views of famous composers of the twentieth century are about the change in the definition of music. In their opinion and according to the definitions and materials available, today’s music expresses human feelings more broadly and appropriately, therefore, musical production is performed more profoundly. According to this new and contemporary view, the development of music is discussed and emphasizes how natural materials are used in their works freely, as well as how artistic studies and their goals are presented to humanity by finding new sound effects and how they are different from the past music. This study discusses (Polyphony), where many sounds are used simultaneously based on the standards of global western music, known as (Classical Music).This research includes Problem, Importance, and Objectives of the study in the first part. The second part is devoted to the definition, and information on several important topics, and discusses the most significant changes that have occurred in the twentieth century. The third section focuses on the elements of melody-harmony, presents the necessary information, the changes that have occurred in these elements, and includes analyses of the examples. This publication then concludes with a presentation of the results and a list of bibliographies.